KEPUASAN MAHASISWA TERHADAP PELAYANAN ADMINISTRASI AKADEMIK PADA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI BANJARMASIN - Padli, Padli; Pebrianto, Agus; Rustaniah, Rustaniah (P3M Politeknik Negeri Banjarmasin, 2019)
The goal of this research is to describe students need academic services during their study provided by administrative staff. Considering the huge numbers of universities, each universities should have their characteristics and competitiveness so that they could maintain their existence. Besides that they need to maintain their quality so that the students will be satisfied with the services provided, thus the vision and mission of the institution could be achieved. The purpose of this research is to know if quality service of academic administration staff at Business Administration Department POLIBAN has an impact to student satisfaction. The sample of this research comprised 200 POLIBAN students at Business Administration Department. The data of this research were collected during the 2018-2019 year. The analysis show that assurance is the only variable who has significant impact to student satisfaction.